KEDUDUKAN HIBAH WASIAT MENURUT HUKUM ISLAM DAN HUKUM PERDATA - Muhammad Husni (Al-Maslahah : Jurnal Ilmu Syariah, 2019)
Testament grants are a problem that often arises in the community. Testamentary grants are seen as virtuous deeds for the culprit because on the one hand the grantee wants to get a reward that continues to flow for him, on the other hand grants are one form of good deeds that is helping people who are given grants. Because the grant is a free gift, the grant must fulfill the stipulated conditions both in Islamic law and civil law. Assets granted by may not exceed one third of the assets owned. This is so that the heirs do not feel harmed. Grants are not allowed to be given to heirs unless there is approval from other heirs. Grants granted by the grantor to other people according to Islamic law are three opinions, which may be withdrawn, may not be withdrawn and may be withdrawn except to other people who are not close relatives. Whereas according to the Civil Law may withdraw the testamentary grant that has been given, because the will start from a party, if the party who testifies is withdrawing its intention, that is normal and permissible. withdrawal here is the same as aborting or canceling his good intentions. In other words, the will be given to someone else, but can be withdrawn.